BATASAN PRIVASI KOMUNIKASI INTERPERSONAL PEREMPUAN MUSLIM BERCADAR DI KOTA MAKASSAR - Tuti Bahfiarti (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2020)
Boudaries of privacy in the context of interpersonal communication is an attempt to disclose themselves openly or closedly to individuals or groups. The purpose of this study is to categorize the privacy boundaries of interpersonal communication of veiled Muslim women in Makassar City. The research method uses a qualitative approach through narrative studies based on stories of veiled Muslim women in conducting social interaction and communication with their external environment. Determination of informants through purposive sampling and primary and secondary data collection. The results showed that the privacy boundaries of interpersonal communication differed based on the sexes of men and women. Social interactions and communication with fellow veiled friends are more open compared to low male friends. The contributing factors are beliefs, and similarities which determine the openness of communication with the external environment.